Reorganising Friesland Hungaria: A case study - Zoltán Buzády (Journal for East European Management Studies, 2005)
This teaching case study focuses on the shifting of company strategy from the national to the CEE-regional level. Friesland, a Dutch-owned dairy company in Hungary, was extremely successful in the national context since 1993, but the 2004-enlargement of the European Union initiated a process of regional integration across Central European countries. Management has to face new challenges for company strategy (such as regional expansion) and organisational structures (fitting an existing national company to the new international group of businesses). – – Diese Fallstudie veranschaulicht, wie sich Firmenstrategie von nationaler Ebene auf den zentral-europäischen Kontext ausweitet. Friesland Ungarn, ein Molkerei Konzern mit holländischen Eigentümern, war seit der Privatisierung im Jahre 1993 außerordentlich erfolgreich, doch die Osterweiterung der Europäischen Union bewirkte einen über mehrere Länder in der Region übergreifenden Integrationsprozess. Somit musste sich das Managementteam neuen Herausforderungen stellen: Strategische Neuorientierung (Regionale Expansion) sowie Umgestaltung der Organisationsform (bestehende Firmen in das neue Unternehmensnetzwerk zu integrieren).
Keywords: 650; Strategic management; organisational change; EU-enlargement; regional strategies; leadership; case study